Legal Status of Recognition of Children Out of Marriage according to Article 280 KUHPerdata - Febi Ilham Fitra; Dwi Putra Jaya; Hurairah Hurairah; Ana Tasia Pase (Fakultas Hukum Dehasen, 2022)
Child acknowledgment in a formal sense is a form of giving information from a man who declares acknowledgment of his children. Meanwhile, in a material sense, child recognition is a legal act to create a family relationship between the child and the person who admits it. Based on Article 280 of the Civil Code, which says; that with a confession made to a child out of wedlock, a civil relationship arises between the child and his father or mother. This means that there is no legal relationship between the illegitimate child and the